Logo Design as a Strategy to Increase Brand Awareness of “Mukti Collection” - Nungki Maulidiyana (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study aims to design a logo as a strategy to enhance brand awareness for the MSME “Mukti Collection”, which operates in the pet accessories sector. The research is motivated by the absence of a clear visual identity, which has hindered competitiveness in the increasingly saturated digital marketplace. Employing a qualitative approach with a design creation method, the design process followed five key stages: data collection, data analysis, concept development, design development, and implementation. Data were collected through semi-structured interviews with the business owner, observation, and literature review. The resulting logo is based on the initials “M” and “C”, visualized as a cat’s face combined with a hugging gesture, complemented by a bell icon, circular frame, and a yellow and black color palette to represent happiness, prosperity, professionalism, and premium quality. The logo was implemented across digital media, packaging, and merchandise to create a cohesive brand ecosystem. The findings demonstrate that a strategically designed logo can serve as the foundation of a consistent visual identity, strengthen brand image, and enhance consumer brand awareness in the digital era.